The Impact of Implementing a Rural Financial Information System, Clarity of Budget Targets and Internal Control on Accountability for Operational Performance of Village Funds in Labuan Batu Regency - Purba, Elsa Pinika Putri; Nasution, Yenni Samri Juliati; Rahmi Syahriza (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2024)
This research uses quantitative methods using primary data obtained from questionnaire results. The population in the study was all village apparatus, consisting of the village head, regional head, secretary, finance chief, general officer, welfare service chief and government chief. And PTPKD (Village Financial Management Technical Implementer) is responsible for managing village funds, numbering thirty people. Based on the sample using the probability sampling method, thirty respondents were selected from the entire population as a sample. The data collection technique was carried out by distributing questionnaires online using Google Form. The data analysis method uses multiple linear regression with SPSS. The results of the partial test hypothesis of the implementation of the village financial information system, (X1), clarity of budget targets (X2) can have a positive effect on the accountability of operational performance of village funds. Simultaneously research results. Internal control (X3), has no effect on the accountability of operational performance of village funds. Simultaneously research results. And using the F test (simultaneous), this shows that the independent variables (X1, X2, X3) have a positive effect on the dependent variable (Y).